Worship through Infaq and Sadaqah for Education Programs at the Muhammadiyyah Zakat, Infaq, and Sadaqah Institution in Cirebon - Leliya, Leliy; Farhan, Muhammad; Wasman, Wasman; Annisa, Dila; Hakim, Fadlih Abdul (CV. Strata Persada Academia, 2024)
LAZISMU (Lembaga Zakat Infaq dan Shadaqah Muhammadiyah / Muhammadiyah Zakat, Infaq, and Sadaqah Institution) is an amil zakat institution in which its fundraising activities are obtained from zakat, infaq and shodaqoh which are allocated to one of the educational financing programs. In accordance with the mission of Lazismu Tuparev Kedawung, Cirebon Regency, this education financing program is one of the priorities to reduce the number of children dropping out of school. Because education is the best way to improve the quality of a nation's human resources. This study aims to answer the questions that become the formulation of the problem.